Application and comparison of high‐speed countercurrent chromatography and high‐performance liquid chromatography in semi‐preparative separation of decarboxymethyl oleuropein aglycone (3, 4‐DHPEA‐EDA), a bioactive secoiridoid from extra‐virgin olive oil. Issue 2 (15th June 2016) - Jiménez‐Sánchez, Cecilia; Lozano‐Sánchez, Jesús; Brüggemann, Margret; Neves‐Vieira, Mariana; Rodriguez‐Werner, Miriam; Schmalfuß, Eva; Winterhalter, Peter; Segura‐Carretero, Antonio; Fernández‐Gutiérrez, Alberto
Abstract : This paper primarily extends research on applying and comparing high‐speed countercurrent chromatography (HSCCC) and high‐performance liquid chromatography (HPLC) in semi‐preparative isolation of decarboxymethyl oleuropein aglycone (3, 4‐DHPEA‐EDA), a bioactive secoiridoid, from extra‐virgin olive oil (EVOO). An EVOO phenolic extract (EVOO‐PE) was obtained by solid‐phase extraction (SPE), and this extract was subjected to one run using the maximum loading capacity of each methodology without loss of resolution. For this sample set, the HSCCC method proved to be a more efficient approach regarding loading capacity, solvent consumption, and throughput compared with the HPLC method. However, the purity of the target from HPLC was superior to that of HSCCC, as the number of theoretical plates could not match that of HPLC. Therefore, we propose that HPLC should be used when higher purities are required, despite higher costs. In addition, HPLC is orthogonal and complementary to HSCCC, and can often provide straightforward resolution of otherwise difficult separations by HSCCC. Practical applications : Our results indicate that the optimized HSCCC is an economic process, and hence, a good candidate for further scaling‐up to preparative and industrial scales, as long as the chromatographic profile of the sample itself is simple enough to achieve good resolution, or a very high purity of the compound of interest is not required. For those cases, HPLC would provide superior target purity but would result in higher costs. This paper compares high‐speed countercurrent chromatography (HSCCC) and high‐performance liquid chromatography (HPLC) in semi‐preparative isolation of decarboxymethyl oleuropein aglycone (3, 4‐DHPEA‐EDA), a bioactive secoiridoid, from extra‐virgin olive oil (EVOO). An EVOO phenolic extract (EVOO‐PE) was obtained by solid‐phase extraction (SPE), and this extract was subjected to one run using the maximum loading capacity of each methodology without loss of resolution. For this sample set, the HSCCC method proved to be a more efficient approach regarding loading capacity, solvent consumption, and throughput compared with the HPLC method. However, the purity of the target from HPLC was superior to that of HSCCC, as the number of theoretical plates could not match that of HPLC. Abstract : This paper compares high‐speed countercurrent chromatography (HSCCC) and high‐performance liquid chromatography (HPLC) in semi‐preparative isolation of decarboxymethyl oleuropein aglycone (3, 4‐DHPEA‐EDA), a bioactive secoiridoid, from extra‐virgin olive oil (EVOO). An EVOO phenolic extract (EVOO‐PE) was obtained by solid‐phase extraction (SPE), and this extract was subjected to one run using the maximum loading capacity of each methodology without loss of resolution. For this sample set, the HSCCC method proved to be a more efficient approach regarding loading capacity, solvent consumption, and throughput compared with the HPLC method. However, the purity of the target from HPLC was superior to that of HSCCC, as the number of theoretical plates could not match that of HPLC.